Self-management of the disease and its role in preventing exacerbations in chronic obstructive pulmonary disease - L. V. Kukol; E. A. Torkatyuk (Туберкулез и болезни лёгких)
Self-management is recognized as an essential tool for providing high-quality care for chronic obstructive pulmonary disease (COPD) and it is usually presented in the action plan as a key component that helps patients to recognize exacerbations and to start treatment early. The patient's ability to independently control and manage changes in symptoms of the disease can provide impact on the quality of life, frequency of exacerbations, admissions to hospital, and lethal outcome. Self-control of the disease is recommended worldwide for patients with COPD, self-management programs are described in numerous studies but they are heterogeneous and the evidence for their effectiveness is contradictory. The review studies various self-management programs for COPD and their effectiveness.